PENGARUH MOBILISASI DINI TERHADAP PERISTALTIK USUS PADA PASIEN POST OP LAPARATOMI - Yosra Sigit Pramono; Meti Agustini (Journal of Nursing Invention, 2021)
ABSTRACT Abstract in English 200-250 words. (Arial 10). To detect spelling and grammar use “select all” and block all abstract paragraph ”tools” “language” choose “English US” or “UK” “detect spelling and grammar. Background: Laparotomy is a surgical incision into the abdominal cavity include herniotomy, gastrectomy, cholecystectomy, duodenostomy, hepatectomy, splenectomy, appendectomy, colostomy. Early mobilization activities encourage fast recovery of intestinal peristaltic because mobilization activities affect cardiovascular, respiratory, and metabolic systems. Objective: to identify the effect of early mobilization on intestinal peristaltic on post-op laparotomy patients at Ulin General Hospital Banjarmasin Method: Pre-experimental design with pretest and posttest (one group pre-post test design). Total sample in the study are 14 people, the data collection method was carried out by non-probability sampling, namely Accidental Sampling Result: Paired Sample T-Test shows p : 0.000 < 0.05 indicates early mobilization affects on intestinal peristalsis Conclusion: There is an effect of early mobilization on intestinal peristalsis on post-op laparotomy patients. Keywords: Laparotomy, early mobilization, intestinal peristaltic